Changes in the Small Noncoding RNAome During M1 and M2 Macrophage Polarization - Ma, Ding; Zhou, Xing; Wang, Yu; Dai, Liming; Yuan, Jie; Peng, Jianping; Zhang, Xiaoling; Wang, Chuandong (Frontiers in Immunology, 2022)
Macrophages belong to a special phagocytic subgroup of human leukocytes and are one of the important cells of the human immune system. Small noncoding RNAs are a group of small RNA molecules that can be transcribed without the ability to encode proteins but could play a specific function in cells. SncRNAs mainly include microRNAs (miRNAs) and piwi-interacting RNAs (piRNAs), small nucleolar RNAs (snoRNAs), small nuclear RNAs (snRNAs) and repeat RNAs. We used high-throughput sequencing analysis and qPCR to detect the expression changes of the small noncoding RNAome during macrophage polarization. Our results showed that 84 miRNAs and 47 miRNAs with were downregulated during M1 macrophage polarization and that 11 miRNAs were upregulated and 19 miRNAs were downregulated during M2 macrophage polarization. MiR-novel-3-nature and miR-27b-5p could promote expression of TNF-α which was marker gene of M1 macrophages. The piRNA analysis results showed that 69 piRNAs were upregulated and 61 piRNAs were downregulated during M1 macrophage polarization and that 3 piRNAs were upregulated and 10 piRNAs were downregulated during M2 macrophage polarization. DQ551351 and DQ551308 could promote the mRNA expression of TNF-α and DQ551351overexpression promoted the antitumor activity of M1 macrophages. SnoRNA results showed that 62 snoRNAs were upregulated and 59 snoRNAs were downregulated during M1 macrophage polarization, whereas 6 snoRNAs were upregulated and 10 snoRNAs were downregulated during M2 macrophage polarization. Overexpression of snoRNA ENSMUST00000158683.2 could inhibit expression of TNF-α. For snRNA, we found that 12 snRNAs were upregulated and 15 snRNAs were downregulated during M1 macrophage polarization and that 2 snRNAs were upregulated during M2 macrophage polarization. ENSMUSG00000096786 could promote expression of IL-1 and iNOS and ENSMUSG00000096786 overexpression promoted the antitumor activity of M1 macrophages. Analysis of repeat RNAs showed that 7 repeat RNAs were upregulated and 9 repeat RNAs were downregulated during M1 macrophage polarization and that 2 repeat RNAs were downregulated during M2 macrophage polarization. We first reported the expression changes of piRNA, snoRNA, snRNA and repeat RNA during macrophage polarization, and preliminarily confirmed that piRNA, snoRNA and snRNA can regulate the function of macrophages.